Characteristics of Charcoal Briquettes from Rajumas Wood Saw Waste (Duabanga moluccana Blume.) with Comparison of Molass Adhesive Composition - Rosadi, M. Kudsi; Wulandari, Febriana Tri; Ningsih, Rima Vera (Jurnal Biologi Tropis, 2025)
Characteristics of Charcoal Briquettes from Rajumas Wood Saw Waste (Duabanga moluccana Blume.) with Comparison of Molass Adhesive Composition